PENGARUH STRES AKADEMIK TERHADAP KUALITAS TIDUR MAHASISWA SEMESTER AKHIR INSTITUT AGAMA ISLAM SUMATERA BARAT - Insani, Syaibatul; Nurva Dillatul Vatin; M. Hubbal Khair; Ismawati Sitorus (Institut Agama Islam Sumatera Barat, 2025)
This study aims to determine the effect of academic stress on sleep quality of final semester students at the Islamic Institute of West Sumatra Pariaman. The research method used a quantitative approach with a simple regression design. The research sample consisted of 57 final semester students taken using saturated sampling technique. Data collection used academic stress scale modified from Gadzella and Masten (2005) and sleep quality scale modified from Buysse et al. (1989). The results showed that there was no significant effect between academic stress and student sleep quality (sig. value 0.358 > 0.05). The coefficient of determination (R Square) of 0.015 indicates that academic stress only contributed 1.5% to sleep quality, while 98.5% was influenced by other factors. These findings indicate that students' sleep quality is more influenced by factors outside academic stress, such as daily habits and environmental factors.